INSTITUTIONAL FUNDAMENTALS OF WASTE MANAGEMENT IN UKRAINE - Zapukhliak, Ivanna Bogdanivna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article proves that in today's conditions economic development should take place in the field of efficient use of resources, conservation of natural ecosystems, flexibility and safety of energy needs of mankind. In contrast to the linear economy, there is a circular economy, which provides for the reduction of resource use and the advantage of renewable materials; the most efficient use of products; recovery of by-products and waste for further use. It is established that inefficient waste management in Ukraine creates significant risks for the environment and the population. A review of the concept of "waste", "waste management system", as well as an analysis of regulatory aspects of waste management in Ukraine, including at the regional level. The main purpose of the research is to find ways to improve the waste management system in Ukraine. Waste classification, waste operations and hierarchy of waste management are considered, which became the basis for the formation of the waste management system, in particular, the principles of its construction, subjects and objects of management are outlined. It is substantiated that the construction of a waste management system at the regional level will allow to form a logical, cost-effective system that will have a significant impact on the development of local communities. The stages of formation of the normative base of waste management in Ukraine are studied, the priority measures on development of the infrastructure of waste management are established, the stages of implementation of the regional plan of waste management are considered. It has been established that the issues of mandatory separate sorting of household waste, introduction of an extended producer responsibility system, tools to raise public awareness, lack of a system of control and responsibility in the field of waste management, needs to adhere to the hierarchy of waste management, needs to be developed waste management infrastructure and the level of transparency in waste management is unsatisfactory.